The Relationship between Self-Regulated Learning and Students' Critical Thinking Skills - Atmojo, Idam Ragil Widianto; Ardiansyah, Roy; Adi, Fadhil Purnama; Chumdari, Chumdari; Saputri, Dwi Yuniasih; Wahyuningtyas, Maria (Universitas Pendidikan Indonesia, 2023)
Self-regulated learning can provide self-reinforcement in gaining academic achievement which in this case is the ability to solve problems by using critical thinking skills. Students need to know their characteristics so they can plan learning strategies and self-regulation processes according to their characteristics so that their critical thinking skills can improve. The purpose of this research is to determine the level of conscientiousness and self-regulated learning (SRL) of university students in the elementary school teacher education study program at Sebelas Maret University. The research sample was 105 students from the class of 2022. The data collection technique used was a test. The data analysis used inferential statistical analysis. The results showed that the SRL of the students was 35% which was mostly in the medium category, while their critical thinking was 35% and mostly in the low category. Based on the Kendal Tau correlation test, the relationship between SRL and critical thinking skills was 0.000 0.05. The results of this research can be used as a reference to measure the correlation between SRL and the critical thinking of university students.